Solve (x + 3)((x - 3) = 7

A. x = 1, -1

B. x = 2, -2

C. x = 5, -5

D. 3, -3

E. 4, -4

#### Top Answer

The answer is : E (4,-4) If you... View the full answer

#### Sign up to view the full answer

#### Other Answers

The way to answer this question is ... View the full answer

Here is a detailed explanation... View the full answer

Here is the solution... View the full answer

The best way to approach your question... View the full answer

The solutions of the equation... View the full answer